Study of Lactococcus lactis and Lactobacillus casei Probiotics Addition on Analysis of Laying Hens Strain Isa Brown Infected with E. coli - Khoirul Huda; Hamzah Nata Siswara; Teguh Dwi Putra; Lia Nur Aini (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
This study aims to determine the use of probiotics Lactococcus lactis and Lactobacillus casei. on the analysis of laying hens infected with Escherichia coli. A total of 120 laying hens aged 25 weeks were divided into 6 treatments. Each treatment included 4 repetitions, each of which included 5 laying hens. The treatments included factor a, namely infectious and non-infectious escherichia coli and factor B, namely AGP, basal feed and probiotics.. The result of this research shows that the use of probiotics Lactococccuslactis and Lactobacillus caseion the laying hens infected with bacteria Escherichia coli The results of the study that giving probiotics had a significant effect (P<0.05) on variable costs, acceptance and profits. The infection factor had a significant effect (P<0.05) on variable costs, revenues and profits. Based on the results of this research, it can be concluded that the addition of probiotic Lactococccuslactis and Lactobacillus casei on the laying hens infected with bacteria Escherichia coli can bacteri increases the income of laying hens.